Contrast-induced nephropathy (CIN) - epidemiology, risk factors and prevention - Pierzchała, Jakub Rafał; Bednarz, Katarzyna; Banaś, Patryk; Sobańska, Natalia; Banasiak, Aleksandra Paulina; Teichman, Rafał; Kasprowicz, Jakub; Abram, Kamila; Adamus, Justyna; Hyjek, Michał (Journal of Education, Health and Sport, 2022)
Introduction: Contrast-induced nephropathy is one of the most serious adverse effects of radiocontrast agents usage. It is currently listed in the literature as the third most common cause of iatrogenic acute kidney injury. Aim of the study: The aim of this study is to provide an overview of the extent, severity and prevention of CIN. It is to shed a broader light on this disease entity and be a helpful resource in the future for other clinicians struggling with CIN. Methods and materials: A literature review was conducted using the PubMed database, using the keywords: "contrast-induced nephropathy"; "acute kidney injury"; "contrast media". Results: Pathogenesis of CIN is not entirely clear. There are many risk factors being e.g. diabetes, chronic kidney disease, advanced age (patients over 75 years old). Prevention methods include restricting contrast volume to a minimum, balancing the patient’s volaemia before contrast administration or perioperative saline hydration to normalise volaemia. Conclusion: CIN is a significant health problem, which can be a life threat. Despite the fact that the exact pathogenesis of the condition still remains unknown, the CIN prophylaxis becomes more and more effective due to better recognition of risk factors and the usage of adequate prevention measures appropriate to the patients’ condition. More studies, with larger test groups, are needed to better define both the pathomechanism of contrast-induced acute kidney injury and new, more effective ways of prevention and treatment of this condition.